Ultrastructure of male accessory glands of chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) - Kabkaew L. Sukontason (2018)
The ultrastructure of the male accessory glands of the blow fly, Chrysomya megacephala (Fabricius), was presented using light microscopy (LM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). A pair of accessory glands was separated at opposite sites. Morphometric results using LM yield evidenced no significant difference in the median of either length or width of the left and right glands. A significant increment in both length and width was seen to plateau between three to six days. SEM observation showed that the surface of the glands revealed a faint irregular groove pattern throughout, and it was occasionally penetrated by tracheoles. Each gland was a slender, elongated sac-like tubule having apical rounded ends, with a slight constriction at the sub-apical part of the gland being observed occasionally. TEM analyses of three-day-old males showed that the glands consisted of external capsular cells with a basement membrane underneath, glandular cells, and gland lumen. The capsular cell was flat and contained a nucleus with electron dense material in the nuclear envelope. The glandular cell, appearing as columnar, consisted of a vacuolated component that contained a large oval nucleus centrally or sub-basally located, with dense mitochondria, numerous rough endoplasmic reticulum, and secretory vesicles containing electron-lucent materials. In the gland lumen, the cross-section through the middle portion revealed dense secretory materials, characterized by electron-dense materials. Some sections revealed a large lumen where secretion accumulates within the delicate sac. The seven-day-old glands exhibited a remarkable change in the lumen, where the whole space contained a large amount of secretory materials, with the electron-dense materials being characterized as similar to those observed in three-day-old glands. About four prominent types of secretions were observed on the basis of difference in electron-density.